Social Media Promotion and Women’s Purchase Intentions for Local Fashion Brands - Rachman, Sitti Hartini; Putri, Nur Vadila (Forum Kerjasama Pendidikan Tinggi, 2025)
This study aims to analyze the impact of social media promotion on trust, perceived value, and consumers' purchase intentions, as well as to evaluate the roles of trust and perceived value as mediators between social media promotion and purchase intentions for local women’s fashion brands in South Sulawesi. This research employs a quantitative approach involving 110 consumers from three main areas: Makassar City, Maros Regency, and Gowa Regency. Data were collected using a questionnaire through purposive sampling. Data analysis was conducted using Structural Equation Modeling (SEM-AMOS) and the Sobel test to assess mediation effects. The results indicate that social media promotion positively and significantly influences the enhancement of trust and perceived value. However, the direct effect of social media promotion on purchase intention is not significant. Indirectly, social media promotion significantly increases purchase intention through perceived value, while its effect through trust is not significant. Perceived value has a dominant influence on purchase intention compared to trust and social media promotion. Although trust does not directly affect purchase intention, it serves as a key factor in enhancing perceived value, which ultimately impacts purchase intention.